Recombinant FimH Adhesin Demonstrates How the Allosteric Catch Bond Mechanism Can Support Fast and Strong Bacterial Attachment in the Absence of Shear. Issue 17 (15th September 2022) - Thomas, Wendy E; Carlucci, Laura; Yakovenko, Olga; Interlandi, Gianluca; Le Trong, Isolde; Aprikian, Pavel; Magala, Pearl; Larson, Lydia; Sledneva, Yulia; Tchesnokova, Veronika; Stenkamp, Ronald E.; Sokurenko, Evgeni V.
Graphical abstract: Highlights: Bacteria use adhesive proteins to bind host cell receptors to cause infection. Both fast and strong binding is mediated by a switch in the adhesin conformation. The conformational switch involves allosteric activation of the adhesive domain. The allosteric activation requires separation from the anchoring domain. The domain separation is the basis of 'catch bonds' but also occurs without force. Abstract: The FimH protein of Escherichia coli is a model two-domain adhesin that is able to mediate an allosteric catch bond mechanism of bacterial cell attachment, where the mannose-binding lectin domain switches from an 'inactive' conformation with fast binding to mannose to an 'active' conformation with slow detachment from mannose. Because mechanical tensile force favors separation of the domains and, thus, FimH activation, it has been thought that the catch bonds can only be manifested in a fluidic shear-dependent mode of adhesion. Here, we used recombinant FimH variants with a weakened inter-domain interaction and show that a fast and sustained allosteric activation of FimH can also occur under static, non-shear conditions. Moreover, it appears that lectin domain conformational activation happens intrinsically at a constant rate, independently from its ability to interact with the pilin domain or mannose. However, the latter two factors control the rate of FimH deactivation. Thus, the allosteric catch bond mechanism can be a much broader phenomenon involved in both fast and strong cell-pathogen attachments under a broad range of hydrodynamic conditions. This concept that allostery can enable more effective receptor-ligand interactions is fundamentally different from the conventional wisdom that allostery provides a mechanism to turn binding off under specific conditions.